Accelerated learning: penggunaan tipe master dalam pembelajaran teori musik dasar - Putra, Zakarias Aria Widyatama; Dewantara, Jagad Aditya (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
In fundamental music theory, comprehension of how music works is tested in two ways: textual (terms) and contextual (application), when students do not grasp the content and instead focus on learning. As a result, when students create musical arrangements and composition tasks, they are unable to organise melodic, rhythmic, and harmonic arrangements in a fundamentally and elegantly organised manner. The usage of accelerated learning with the MASTER type is believed to provide a remedy to students' confusion about basic music theory. This study employed a descriptive qualitative method and a case study methodology. The research subjects are first-year students of Tanjungpura University's Performing Arts Education Study Programme (FKIP). In-depth observation and direct interviews provided case descriptions in learning. Source triangulation and interactive model analysis were used to determine data validity. Based on the MASTER type's application in learning fundamental music theory, students have had the most impact when they utilise their minds and bodies, create knowledge, and collaborate with others. This is significant because the foundation for shaping students' skills in the twenty-first century is based on students as learners and the shift from constructivism to behaviourism.